2015
DOI: 10.1002/pon.3757
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of end-of-life prognostic communication needs as reported by widowed fathers due to cancer

Abstract: Objective Effective physician communication about prognosis is a critical aspect of quality care for families affected by terminal illness. This is particularly important for spousal caregivers of terminally ill parents of dependent children, who may have unique needs for communication about anticipated death. The objective of this study was to explore end-of-life prognostic communication experiences reported by bereaved fathers whose wives died from cancer. Methods From October 2012 to November 2013 we surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(57 citation statements)
references
References 24 publications
(25 reference statements)
0
55
0
2
Order By: Relevance
“…The impact of early discussions can also extend to those close to patients prior to death, and into bereavement. In a recent US qualitative study, family members stated that timely end-of-life care discussions enabled them to make the most of the time they had with the patient, and make use of hospice and palliative care services sooner 21. In addition, having such conversations before the patient becomes too unwell can be crucial in allowing relatives to prepare for death while also maintaining hope 22.…”
Section: Why Are End-of-life Care Discussion So Important?mentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of early discussions can also extend to those close to patients prior to death, and into bereavement. In a recent US qualitative study, family members stated that timely end-of-life care discussions enabled them to make the most of the time they had with the patient, and make use of hospice and palliative care services sooner 21. In addition, having such conversations before the patient becomes too unwell can be crucial in allowing relatives to prepare for death while also maintaining hope 22.…”
Section: Why Are End-of-life Care Discussion So Important?mentioning
confidence: 99%
“…Research suggests that information must be honest, while maintaining hope,21 34 38 45 but not so much hope that it gives unrealistic expectations 21 34. Information should be delivered in a way that shows empathy, but not pity,45 in a manner that is candid but not blunt 21 35 46. With regard to terminology, research has suggested that explicit phrasing can lead to distress for some family members, while for others more figurative or indirect phrasing can lead to miscommunication 47.…”
Section: Why Do Clinicians Find These Discussion So Difficult?mentioning
confidence: 99%
See 1 more Smart Citation
“…Such conversations can help meet the dying parent’s goals of care,[19] identify areas of parenting concern, help the surviving parent with parenting,[27] and facilitate children’s adjustment. [27, 28] Pre-death conversations that anticipate future challenges may reduce the surviving parent’s psychological distress in bereavement.…”
Section: Discussionmentioning
confidence: 99%
“…[1618] Findings from our previous studies on bereaved fathers suggest there is inadequate communication between terminally ill mothers and their families. [19, 20] A majority of widowed fathers with dependent children reported that their wife did not say goodbye to their children prior to death. [20] Given the importance of parenting roles and parenting responsibilities for dying parents, it is imperative to understand parents’ communication priorities at the EOL.…”
Section: Introductionmentioning
confidence: 99%